The economics of grief - Gerard J. van den Berg; Petter Lundborg; Johan Vikström (Institute for the Study of Labor (IZA), 2012)
We study the short-run and long-run economic impact of one of the largest losses that an individual can face; the death of a child. We utilize unique merged registers on the entire Swedish population, combining information on the date and cause of death with parents' labor market outcomes, health outcomes, marital status, and subsequent fertility. We exploit the longitudinal dimension of the data and deal with a range of selection issues. We distinguish between effects on labor and various non-labor income components and we consider patterns over time. We find that labor market effects are persistent.
Keywords: I12; I11; J14; J12; C41; 330; bereavement; labor supply; child mortality; depression; sickness absenteeism; employment; marriage; death; divorce; mental health; fertility